2021
DOI: 10.3389/fimmu.2021.701409
|View full text |Cite
|
Sign up to set email alerts
|

Non-Typhoidal Salmonella and the Risk of Kawasaki Disease: A Nationwide Population-Based Cohort Study

Abstract: ObjectiveThe aim of this study was to investigate the relationship between non-typhoidal Salmonella (NTS) infection and the risk of Kawasaki disease (KD) by using a nationwide population-based data set in Taiwan.MethodsIn this retrospective cohort study, we enrolled 69,116 patients under 18 years of age, with NTS from January 1st, 2000, to December 31st, 2013, using the population-based National Health Insurance Research Database of Taiwan. A comparison group without NTS was matched (at a 1:4 ratio) by propens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…[ 8 10 ] In this study, 68.34% of children are under 3 years old, which is consistent with the research results of most scholars. [ 2 , 11 ] It can be seen from the comparison of age distribution of KD and IKD that there is no significant statistical difference between the 2, indicating that the age distribution of IKD and KD is consistent. Relevant studies showed that KD has a special male susceptibility.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[ 8 10 ] In this study, 68.34% of children are under 3 years old, which is consistent with the research results of most scholars. [ 2 , 11 ] It can be seen from the comparison of age distribution of KD and IKD that there is no significant statistical difference between the 2, indicating that the age distribution of IKD and KD is consistent. Relevant studies showed that KD has a special male susceptibility.…”
Section: Discussionmentioning
confidence: 95%
“…Kawasaki disease (KD) is an acute febrile and eruptive disease with systemic small and medium-sized arteritis as the main pathological change. [ 1 , 2 ] At present, the cause of the disease is unknown, and it is mostly detected in Asian children under 5 years old. [ 1 , 3 ] Coronary artery lesions (CAL) are common complications of KD, which can lead to ischemic heart disease, myocardial infarction, sudden death and other serious consequences.…”
Section: Introductionmentioning
confidence: 99%